Which Are Effective Teaching Strategies to Change Preconceptions in Geography? An Empirical Study on Conceptual Change About Groundwater - Reinfried, Sibylle (Journal of Geography Education, 2007)
This study investigates the impact of different teaching approaches on conceptual change in geography. By using the mental model-building strategy, a moderate constructivist approach, the author could show in her previous research that preconceptions concerning groundwater occurrence in nature could be changed efficiently. Subsequently the question arose whether a cognitivist approach, based on guided instruction, would be equally efficient, if teaching strategies were chosen that have empirically proved their high efficacy for learning. A quasi-experimental research design was chosen to teach two classes of 14-year old secondary students at a Zurich high school. One class was taught in a more constructivist way, the other in a guided approach using a number of cognitivist strategies. The statistical analysis of the data that was gained through quantitative and qualitative methods, revealed a significant impact on conceptual change independently of the teaching method. Significant changes related to one or the other teaching method could not be found. The study confirmed results of other researcher who found that conceptual change could be induced through different teaching and learning approaches, as long as they help the learners to grasp new knowledge, to process it and to connect it with their existing knowledge. Additionally it is crucial to offer opportunities for self-regulated and self-reliant learning. It's a challenge for geography education to establish such new teaching approaches in every day teaching practice. To master this challenge the discipline has to become aware of the findings of pedagogical psychology about teaching and learning and to integrate these findings into geography education to contribute substantially to the professional development of geography teachers.